Assistive technology for people with deafblindness in Southern Africa: a Delphi study exploring dimensions of impact. (2nd January 2023) - Bell, Diane; Prain, Meredith; Layton, Natasha
Abstract: Purpose: Assistive technology (AT) is a highly effective intervention to address the capability gap for people living with deafblindness. The My AT Outcomes Framework (MyATOF) is a novel Australian framework founded upon AT process principles and outcomes research. It guides stakeholders to articulate AT use according to 6 dimensions. MyATOF was developed as a data collection and knowledge translation tool. The use case of AT by people with deafblindness in Southern Africa was investigated in this study to determine the applicability of MyATOF dimensions to (a) people with deafblindness and (b) low- and middle-income countries. Materials and methods: Two online surveys, using the Delphi methodology, were undertaken with key stakeholders including people with deafblindness, family members, researchers, service providers, educators and advocates. An expert panel of 17 completed Phase 1, with 14 completing Phase 2. The WHO 5 Ps AT systems thinking model was used in data analysis. Results: Respondents affirmed the validity of the dimensions of MyATOF for people with deafblindness in four Southern African countries. In-country barriers and constraints were identified as significantly impacting the capacity of AT users with deafblindness, to realize positive outcomes. Conclusions: The MyATOF dimensions show promise in their use with persons with deafblindness in Southern Africa, though further research is needed. IMPLICATIONS FOR REHABILITATION: The impact of assistive technology and related supports can be evaluated across a number of dimensions including human rights, costs incurred and saved, consumer experience, and service delivery satisfaction. These dimensions of impact resonate across the two continents investigated to date, with contextual factors being considered. Variables influencing access to assistive technology across contexts can be understood through the WHO GATE five P's systems thinking model. Few tools place data capture and outcomes measurement in the hands of assistive technology users, but indications are that this is of value to consumers.